Dutch food bank parcels do not meet nutritional guidelines for a healthy diet. Issue 3 (27th May 2016) - Neter, Judith E.; Dijkstra, S. Coosje; Visser, Marjolein; Brouwer, Ingeborg A.
Abstract: Nutritional intakes of food bank recipients and consequently their health status largely rely on the availability and quality of donated food in provided food parcels. In this cross-sectional study, the nutritional quality of ninety-six individual food parcels was assessed and compared with the Dutch nutritional guidelines for a healthy diet. Furthermore, we assessed how food bank recipients use the contents of the food parcel. Therefore, 251 Dutch food bank recipients from eleven food banks throughout the Netherlands filled out a general questionnaire. The provided amounts of energy (19 849 (sd 162 615) kJ (4744 (sd 38 866) kcal)), protein (14·6 energy percentages (en%)) and SFA (12·9 en%) in a single-person food parcel for one single day were higher than the nutritional guidelines, whereas the provided amounts of fruits (97 (sd 1441) g) and fish (23 (sd 640) g) were lower. The number of days for which macronutrients, fruits, vegetables and fish were provided for a single-person food parcel ranged from 1·2 (fruits) to 11·3 (protein) d. Of the participants, only 9·5 % bought fruits and 4·6 % bought fish to supplement the food parcel, 39·4 % used all foods provided and 75·7 % were (very) satisfied with the contents of the food parcel. Our study shows that the nutritional content of food parcels provided by Dutch food banks is not in line with the nutritional guidelines. Improving the quality of the parcels is likely to positively impact the dietary intake of this vulnerable population subgroup.